Semicircular long-strip-shaped solar panel and preparation method thereof
By adopting new CPC materials and optimizing the design of EVA layers in solar panels, the problems of large weight and poor weather resistance of traditional solar panels are solved, high light transmittance and anti-aging properties are achieved, suitable for complex terrain installations, and installation efficiency is improved and lifespan.
Patent Information
- Application Number
- CN202411375288.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-17
AI Technical Summary
Traditional solar panels have high weight, difficult installation, poor weather resistance, difficult to meet the installation needs of complex terrain, and low adhesion between the back panel and EVA affects life.
Designed with semicircular long strip solar panels, using new CPC materials as back panels, combining specific fluorocarbon resins, polyisocyanate resins and modified titanium dioxide, improve light transmittance and anti-aging by optimizing the film layer structure and crosslinking density. zirconium hydrogen phosphate of different particle sizes is added to the EVA layer to enhance moisture and heat aging resistance.
It realizes the high light transmittance, excellent weather resistance and aging resistance of solar panels, reduces wind resistance and installation costs, improves installation efficiency and wind and hail resistance, and extends service life.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar back panels, and in particular relates to a semicircular long strip solar panel and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly severe environmental problems, the development and utilization of solar energy as a clean and renewable energy has received widespread attention. As the core component of the solar power generation system, the performance and quality of solar panels directly affect the power generation efficiency and stability of the entire system. Traditional solar panels are mostly rectangular or square. Although they are simple in design and easy to manufacture, there are still some problems in practical applications.
[0003] Traditional solar panels are mostly double-glass double-sided photovoltaic modules, which are not only heavy and not conducive to installation and transportation, but also unable to prevent the back-transmitted ultraviolet rays from damaging the back packaging materials and solar cells. At the same time, the shape and size of traditional solar panels are relatively fixed, which is difficult to meet the diverse installation needs, especially when installed on complex terrain or irregular surfaces, requiring additional brackets and fixtures, which increases the installation cost and difficulty. In addition, the solar back panel has poor weather resistance and is prone to yellowing after aging, which will affect the light transmittance and thus the power generation effect. The low adhesion between the back panel and EVA will also affect the life of the solar panel.
[0004] Therefore, there is a need for a semicircular long strip solar panel that can not only improve the comprehensive performance and service life of the solar panel, but also reduce production costs and improve installation efficiency. Summary of the invention
[0005] The purpose of the present invention is to provide a semicircular long strip solar panel and a preparation method thereof, which adopts a new CPC material as a back plate, which not only has high transmittance, but also has excellent weather resistance and aging resistance, and is easy to process and shape. The prepared solar panel is not only beautiful, but also greatly reduces wind resistance and improves use efficiency. At the same time, the solar panel is light in weight, low in installation cost, convenient and quick to install, strong in wind resistance and hail resistance, and is suitable for installation on the surface of cylindrical objects.
[0006] A semicircular long strip solar panel comprises, from bottom to top, a glass fiber board / PTE layer, an EVA layer, a strip battery sheet, an EVA layer, and a CPC layer.
[0007] Preferably, the thickness of the EVA layer is 120-170 μm.
[0008] Preferably, the CPC layer includes a PET base film and film layers on both sides of the PET base film.
[0009] Preferably, the PET base film has a thickness of 100-150 μm, a light transmittance of ≥85%, and a UV light blocking rate of 250-360 nm of ≥90%.
[0010] In some preferred embodiments, the PET base film is purchased from Jiangsu Yuxing Film Technology Co., Ltd.
[0011] Preferably, the film layer has a thickness of 15 to 30 μm.
[0012] Preferably, the raw materials for preparing the film layer, by weight percentage, are 40% to 50% fluorocarbon resin, 10% to 15% curing agent, 0.1% to 2% dispersant, 10% to 20% modified titanium dioxide, 0.1% to 0.5% leveling agent, and the solvent is added to make up the remainder to 100%.
[0013] Preferably, the fluorocarbon resin includes a first fluorocarbon resin and a second fluorocarbon resin.
[0014] Preferably, the mass ratio of the first fluorocarbon resin to the second fluorocarbon resin is 1:(0.5-2); more preferably, it is 1:1.
[0015] Preferably, the first fluorocarbon resin has a solid content of 59% to 61%, a hydroxyl value of 33 to 43 mgKOH / g, a number average molecular weight of 12,000 to 16,000, an acid value of less than 1 mgKOH / g, and a viscosity of 500 to 1,000 cp.
[0016] In some preferred embodiments, the first fluorocarbon resin is purchased from Changxing Chemical Co., Ltd., Taiwan, China, 41016S.
[0017] Preferably, the second fluorocarbon resin has a solid content of 49% to 51%, a hydroxyl value of 49 to 59 mgKOH / g, a viscosity of 340 to 500 cp, a fluorine content of 22% to 24%, and a number average molecular weight of 15,000 to 20,000.
[0018] In some preferred embodiments, the second fluorocarbon resin is purchased from Changxing Chemical Co., Ltd., Taiwan, China, 4103.
[0019] The inventors found that the use of two specific fluorocarbon resins as the raw materials of the CPC layer film can improve the light transmittance of the CPC layer while improving its weather resistance and anti-yellowing properties. This may be because the two fluorocarbon resins react chemically during the cross-linking process to form a more complex and stable chemical structure, which not only enhances the overall strength of the CPC layer, but also makes its molecular chain more compact, reduces defects and gaps, thereby improving the light transmittance and weather resistance of the CPC layer. At the same time, by adjusting the ratio of the two resins, the cross-linking density of the film layer can be adjusted, thereby optimizing the microstructure of the CPC layer, helping to improve the weather resistance and anti-yellowing properties of the CPC layer, and reducing the yellowing phenomenon caused by oxidation, ultraviolet rays and other factors. In the experiment, the ratio of the two resins needs to be controlled. If the hydroxyl content in the system is too high, the cross-linking density of the formed coating is too large, the coating becomes brittle, and the aging resistance is affected. On the other hand, a low hydroxyl content will result in a cross-linking density that is too small, and the film layer is easily degraded after aging.
[0020] Preferably, the curing agent is polyisocyanate resin.
[0021] Preferably, the polyisocyanate resin is an aliphatic polyisocyanate resin containing hexamethylene diisocyanate.
[0022] Preferably, the NCO content of the polyisocyanate resin is 23% to 24%, the viscosity at 23° C. is 630 to 860 mPa·s, and the content of hexamethylene diisocyanate monomer is less than 0.25%.
[0023] In some preferred embodiments, the polyisocyanate resin is purchased from Covestro, N3900.
[0024] The inventor found that, by selecting specific polyisocyanate resin as curing agent, not only can the structural stability of CPC layer be improved, but also the adhesion between film and EVA layer can be improved. This may be because the isocyanate group (NCO) on polyisocyanate resin reacts with the active hydrogen atoms (such as hydroxyl, amino etc.) in CPC layer film and EVA layer to form a stable covalent bond, thereby improving the stability of film and the adhesion with EVA layer. Meanwhile, there is no H on the N atom of the aliphatic polyisocyanate resin containing hexamethylene diisocyanate, and it will not break under the irradiation of ultraviolet light, so the ultraviolet stability is high. In addition, by controlling the content of NCO in polyisocyanate resin, the hydrolysis resistance and adhesion of film can be improved. But too much NCO can react with water to generate the chemical bonds with poor wet heat stability such as biuret, allophanate bond, thereby causing the film to significantly reduce the adhesion with substrate and EVA layer after wet heat aging.
[0025] Preferably, the solid content of the dispersant is 50% to 54%, and the viscosity at 40°C is 26 to 28 mm 2 / s.
[0026] In some preferred embodiments, the dispersant is purchased from BYK Chemicals, BYK-110.
[0027] The preparation method of the modified titanium dioxide comprises the following steps: hydrolyzing the coupling agent in an ethanol aqueous solution with a concentration of 80 wt / %, adding titanium dioxide, stirring at 55-65° C. for 2-4 hours, filtering, and drying at 100° C. for 12 hours to obtain the modified titanium dioxide.
[0028] Preferably, the volume ratio of the coupling agent to the ethanol aqueous solution is 1:30-50; more preferably, it is 1:40.
[0029] Preferably, the coupling agent is 3-aminopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0030] Preferably, the mass ratio of the 3-aminopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane is 1:(1-3):(3-5); more preferably, it is 1:2:4.
[0031] Preferably, the titanium dioxide has a sieve residue (45 μm sieve opening) of ≤0.1%, a tinting power (Reynolds value) of ≥1850, and an oil absorption of ≤19 / 100 g.
[0032] In some preferred embodiments, the titanium dioxide is purchased from Shanghai Yuanjiang Chemical Co., Ltd., R299.
[0033] Preferably, the added amount of the coupling agent is 2% to 8% of the mass of the titanium dioxide.
[0034] In some preferred schemes, adding an appropriate amount of titanium dioxide to the film layer can reduce the ultraviolet transmittance of the film layer, thereby improving the ultraviolet resistance and aging resistance of the CPC layer. However, the dispersibility of titanium dioxide in the system is poor, which affects the effect. The inventors found that the use of a specific coupling agent to modify titanium dioxide can improve the compatibility of titanium dioxide in the system while also improving the bonding strength between the CPC layer and EVA. This may be because the coupling agent functional groups such as amino, thiol, and acryloxy groups are grafted on the surface of titanium dioxide through modification, which can not only react with the active groups of the organic raw materials in the film layer, thereby generating stronger interactions, improving the interface bonding between the organic raw materials in the film layer and titanium dioxide, and improving the compatibility between titanium dioxide and the organic raw materials in the film layer, thereby improving the ultraviolet resistance and aging resistance of the CPC layer, it can also cross-link with the EVA in the EVA layer, thereby enhancing the bonding force between the CPC layer and the EVA layer. In addition, the silane coupling agent can form a uniform coating on the surface of titanium dioxide particles, which can not only improve the dispersibility of titanium dioxide in the organic matrix, but also prevent its agglomeration and precipitation, thereby improving the stability of the CPC layer.
[0035] Preferably, the leveling agent is an acrylic leveling agent, the effective content is 49% to 51%, and the specific gravity is 0.95 to 0.97 g / cm 3 .
[0036] In some preferred embodiments, the leveling agent is purchased from Suzhou Qingtian New Materials Co., Ltd.
[0037] Preferably, the solvent is butyl acetate.
[0038] The preparation method of the CPC layer comprises the following steps:
[0039] S1. Mix fluorocarbon resin, solvent, dispersant and modified titanium dioxide, disperse them uniformly at high speed, and control the fineness of the mixture by ball milling to be below 5 μm. Add leveling agent for secondary dispersion, add curing agent and mix them uniformly to obtain a film coating.
[0040] S2. After the PET base film is corona-discharged, the film coating is applied on the PET base film. After drying, aging and cooling, the film coating is continuously applied on the other side of the PET base film. After drying, aging and cooling, the CPC layer is obtained.
[0041] Preferably, the specific conditions of drying and aging are: drying temperature 75-85°C, time 3-5h; aging temperature 55-65°C, time 20-30h.
[0042] The raw materials for preparing the EVA layer include, by weight, 95-105 parts of EVA resin, 2-8 parts of crosslinking agent, 0.05-1 part of silane coupling agent, 0.05-0.2 part of ultraviolet light absorber, 0.05-0.1 part of free radical scavenger, and 2-4 parts of inorganic auxiliary agent.
[0043] Preferably, the EVA resin includes a first EVA resin and a second EVA resin.
[0044] Preferably, the mass ratio of the first EVA resin to the second EVA resin is (0.5-2):1; more preferably, it is 1:1.
[0045] Preferably, the vinyl acetate content of the first EVA resin is 27% to 29%, and the melt index is 25 g / 10 min (190° C. / 2.16 kg).
[0046] Preferably, the vinyl acetate content of the second EVA resin is 31% to 33%, and the melt index is 43 g / 10 min (190° C. / 2.16 kg).
[0047] In some preferred embodiments, the first EVA resin and the second EVA resin are both purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0048] The inventors found that the use of two EVA resins as the raw materials of the EVA layer can improve the weather resistance and resistance to wet heat aging of the solar panel. This may be because the two EVA resins work synergistically. During the cross-linking reaction, new chemical bonds are not only formed between different EVA resin molecules, but the formation of these chemical bonds enhances the interaction between molecules, making the composite material more stable when subjected to external forces. In addition, the microstructure of the EVA layer, such as the pore size and porosity, can be adjusted, thereby reducing the air permeability and water permeability of the solar panel, thereby improving its resistance to wet heat aging.
[0049] Preferably, the crosslinking agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and triallyl isocyanurate.
[0050] Preferably, the mass ratio of the 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane to triallyl isocyanurate is (8-10):1; more preferably, it is 9:1.
[0051] Preferably, the silane coupling agent is vinyl tris (2-methoxyethoxy) silane.
[0052] The inventors found that the selection of a specific cross-linking agent can not only improve the cross-linking degree and cross-linking efficiency of the EVA layer, but also improve the anti-aging property. This may be because the synergistic effect between the two cross-linking agents helps to form a more uniform and dense cross-linked network structure, which not only significantly improves the cross-linking degree and cross-linking efficiency of the EVA layer, but also enhances its anti-aging, anti-degradation and other capabilities, thereby improving the weather resistance and stability of the entire solar panel. However, the excessive content of the cross-linking agent will cause the ionization of small polymer molecules in the system to generate ions, increase the carrier density and ion mobility, make the EVA film prone to aging and yellowing, and also cause the bonding performance to decrease. At the same time, the addition of a specific silane coupling agent can not only react with the EVA and CPC layer raw materials to cross-link, increase the bonding strength between the two film layers, and the polar groups thereon are grafted to the EVA molecules, which can also improve the orderliness of the polymer molecules, thereby improving the volume resistivity, thereby improving the stability of the EVA layer and even the entire solar panel.
[0053] Preferably, the ultraviolet light absorber is benzophenone.
[0054] Preferably, the free radical scavenger is 2,6-di-tert-butyl-p-cresol.
[0055] Preferably, the inorganic auxiliary agent is zirconium hydrogen phosphate.
[0056] Preferably, the zirconium hydrogen phosphate includes a first zirconium hydrogen phosphate and a second zirconium hydrogen phosphate.
[0057] Preferably, the average particle size of the first zirconium hydrogen phosphate is 0.5-0.8 μm; more preferably, it is 0.6 μm.
[0058] Preferably, the average particle size of the second zirconium hydrogen phosphate is 1.8-2.2 μm; more preferably, it is 2 μm.
[0059] In some preferred embodiments, the first zirconium hydrogen phosphate and the second zirconium hydrogen phosphate are both purchased from Fujian Ruisen New Materials Co., Ltd.
[0060] Preferably, the mass ratio of the first zirconium hydrogen phosphate to the second zirconium hydrogen phosphate is (2-4):1; more preferably, it is 3:1.
[0061] The inventors found that when preparing the EVA layer, adding zirconium hydrogen phosphate of different particle sizes as an inorganic auxiliary agent can improve the weather resistance of the solar panel. This may be because zirconium hydrogen phosphate not only has good stability itself, but also can be added to the EVA layer system to improve its crystallinity, thereby reducing the ion mobility while increasing the volume resistivity, thereby reducing the aging speed of the EVA layer under environmental factors such as ultraviolet rays and humidity, improving the thermal stability and resistance to wet and hot aging of the solar panel, and extending the service life of the solar panel. At the same time, the addition of zirconium hydrogen phosphate can reduce the volume shrinkage and stress caused by cooling and curing when the EVA layer is bonded, thereby improving the adhesion of the EVA layer. However, too much addition of inorganic auxiliary agents will affect the crosslinking between other raw materials, thereby affecting the adhesion and stability of the EVA layer.
[0062] The method for preparing the semicircular long strip solar panel comprises the following steps:
[0063] S1. After mixing the raw materials for preparing the EVA layer, add toluene, stir and dissolve evenly, and perform ultrasonic treatment for 20 to 30 minutes to obtain an EVA layer solution;
[0064] S2, coating the EVA layer solution on the glass fiber board / PTE layer, drying, aging and cooling;
[0065] S3, coating the EVA layer solution on the CPC layer, drying, aging and cooling;
[0066] S4, placing the strip-shaped battery sheet between two EVA layers, compounding and cross-linking, and then wrapping, fixing and installing.
[0067] Preferably, the added amount of toluene is 8 to 10 times the mass of EVA.
[0068] Preferably, the specific conditions of drying and aging are: drying temperature 75-85°C, time 3-5h; aging temperature 55-65°C, time 20-30h.
[0069] Preferably, the specific conditions of the composite cross-linking are: temperature of 140-160° C., and cross-linking time of 12-18 min.
[0070] Preferably, the radius of the semicircular long strip solar panel is 50-300 mm, and the length is 200-3000 mm.
[0071] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0072] 1. The present invention provides a semicircular long strip solar panel, which uses a new CPC material as a back panel, which not only has high transmittance, but also has excellent weather resistance and aging resistance, and is easy to process and shape. The prepared solar panel is not only beautiful, but also greatly reduces wind resistance and improves use efficiency. At the same time, the solar panel is light in weight, low in installation cost, easy and quick to install, strong in wind resistance and hail resistance, and is suitable for installation on the surface of cylindrical objects.
[0073] 2. The present invention selects two specific fluorocarbon resins as raw materials for the CPC layer film, which can improve the light transmittance of the CPC layer while improving its weather resistance and yellowing resistance.
[0074] 3. The present invention uses a specific polyisocyanate resin as a curing agent, which can not only improve the structural stability of the CPC layer, but also improve the adhesion between the film layer and the EVA layer.
[0075] 4. The present invention selects a specific coupling agent to modify the titanium dioxide, which can improve the compatibility of the titanium dioxide in the system and also improve the bonding strength between the CPC layer and EVA.
[0076] 5. The present invention can improve the weather resistance and moisture-heat aging resistance of the solar panel by selecting two kinds of EVA resins as the raw materials of the EVA layer.
[0077] 6. The present invention selects a specific cross-linking agent, which can not only improve the cross-linking degree and cross-linking efficiency of the EVA layer, but also improve its anti-aging property.
[0078] 7. In the present invention, when preparing the EVA layer, zirconium hydrogen phosphate with different particle sizes is added as an inorganic additive, which can improve the weather resistance of the solar panel. DETAILED DESCRIPTION
[0079] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0080] The raw materials used in the present invention are all commercially available, specifically:
[0081] The PET base film, with a thickness of 125 μm, a light transmittance of 88%, and a UV light blocking rate of 250 to 360 nm of ≥92%, was purchased from Jiangsu Yuxing Film Technology Co., Ltd.
[0082] The first fluorocarbon resin has a solid content of 59% to 61%, a hydroxyl value of 33 to 43 mgKOH / g, a number average molecular weight of 12,000 to 16,000, an acid value of less than 1 mgKOH / g, and a viscosity of 500 to 1000 cp, and is purchased from Changxing Chemical Co., Ltd., Taiwan, China, 41016S.
[0083] The second fluorocarbon resin has a solid content of 49% to 51%, a hydroxyl value of 49 to 59 mgKOH / g, a viscosity of 340 to 500 cp, a fluorine content of 22% to 24%, and a number average molecular weight of 15,000 to 20,000; purchased from Changxing Chemical Co., Ltd., Taiwan, China, 4103.
[0084] Aliphatic polyisocyanate resin containing hexamethylene diisocyanate, NCO content of 23% to 24%, viscosity of 630 to 860 mPa·s at 23° C., hexamethylene diisocyanate monomer content of less than 0.25%, purchased from Covestro, N3900.
[0085] The solid content of the dispersant is 50% to 54%, and the viscosity at 40° C. is 26 to 28 mm 2 / s.
[0086] In some preferred embodiments, the dispersant is purchased from BYK Chemicals, BYK-110.
[0087] Titanium dioxide, sieve residue (45 μm sieve hole) ≤ 0.1%, tinting power (Reynolds value) ≥ 1850, oil absorption ≤ 19 / 100g, purchased from Shanghai Yuanjiang Chemical Co., Ltd., R299.
[0088] Acrylate leveling agent, effective content is 49% to 51%, specific gravity is 0.95 to 0.97 g / cm 3 , purchased from Suzhou Qingtian New Materials Co., Ltd.
[0089] The first EVA resin has a vinyl acetate content of 27% to 29% and a melt index of 25 g / 10 min (190° C. / 2.16 kg); the second EVA resin has a vinyl acetate content of 31% to 33% and a melt index of 43 g / 10 min (190° C. / 2.16 kg); both were purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0090] The first zirconium hydrogen phosphate has an average particle size of 0.6 μm; the second zirconium hydrogen phosphate has an average particle size of 2 μm; both are purchased from Fujian Ruisen New Materials Co., Ltd.
[0091] Example 1
[0092] The present embodiment provides a semicircular strip solar panel, which comprises, from bottom to top, a glass fiber board, an EVA layer, a strip-shaped battery sheet, an EVA layer, and a CPC layer.
[0093] The thickness of the EVA layer is 150 μm.
[0094] The CPC layer includes a PET base film and film layers on both sides of the PET base film.
[0095] The film layer has a thickness of 20 μm.
[0096] The raw materials for preparing the film layer are, by weight percentage, 45% fluorocarbon resin, 12% curing agent, 1% dispersant, 15% modified titanium dioxide, 0.3% leveling agent, and the solvent is added to make up the rest to 100%.
[0097] The fluorocarbon resin includes a first fluorocarbon resin and a second fluorocarbon resin, and the mass ratio of the first fluorocarbon resin and the second fluorocarbon resin is 1:1.
[0098] The curing agent is polyisocyanate resin.
[0099] The polyisocyanate resin is an aliphatic polyisocyanate resin containing hexamethylene diisocyanate.
[0100] The preparation method of the modified titanium dioxide comprises the following steps: hydrolyzing the coupling agent in an ethanol aqueous solution with a concentration of 80 wt / %, adding titanium dioxide, stirring at 60° C. for 3 hours, filtering, and drying at 100° C. for 12 hours to obtain the modified titanium dioxide.
[0101] The volume ratio of the coupling agent to the ethanol aqueous solution is 1:40.
[0102] The coupling agent is 3-aminopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane, and the mass ratio is 1:2:4.
[0103] The added amount of the coupling agent is 5% of the mass of the titanium dioxide.
[0104] The solvent is butyl acetate.
[0105] The preparation method of the CPC layer comprises the following steps:
[0106] S1. Mix fluorocarbon resin, solvent, dispersant and modified titanium dioxide, disperse them uniformly at high speed, and ball-mill them to a fineness of ≤5 μm, add a leveling agent for secondary dispersion, add a curing agent and mix them uniformly to obtain a film coating;
[0107] S2. After the PET base film is corona-discharged, the film coating is applied on the PET base film. After drying, aging and cooling, the film coating is continuously applied on the other side of the PET base film. After drying, aging and cooling, the CPC layer is obtained.
[0108] The specific conditions of the drying and aging are: drying temperature 80° C., time 4 hours; aging temperature 60° C., time 24 hours.
[0109] The raw materials for preparing the EVA layer include, by weight, 100 parts of EVA resin, 5 parts of crosslinking agent, 0.5 parts of silane coupling agent, 0.1 parts of ultraviolet light absorber, 0.08 parts of free radical scavenger, and 3 parts of inorganic auxiliary agent.
[0110] The EVA resin includes a first EVA resin and a second EVA resin, and the mass ratio of the first EVA resin and the second EVA resin is 1:1.
[0111] The crosslinking agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and triallyl isocyanurate, and the mass ratio is 9:1.
[0112] The silane coupling agent is vinyl tris (2-methoxyethoxy) silane.
[0113] The ultraviolet light absorber is benzophenone.
[0114] The free radical scavenger is 2,6-di-tert-butyl-p-cresol.
[0115] The inorganic auxiliary agent is zirconium hydrogen phosphate.
[0116] The zirconium hydrogen phosphate includes a first zirconium hydrogen phosphate and a second zirconium hydrogen phosphate, and the mass ratio is 3:1.
[0117] The method for preparing the semicircular long strip solar panel comprises the following steps:
[0118] S1. Mix the raw materials for preparing the EVA layer, add toluene, stir and dissolve evenly, and perform ultrasound for 25 minutes to obtain an EVA layer solution;
[0119] S2, coating the EVA layer solution on the glass fiber board / PTE layer, drying, aging and cooling;
[0120] S3, coating the EVA layer solution on the CPC layer, drying, aging and cooling;
[0121] S4, placing the strip-shaped battery sheet between two EVA layers, compounding and cross-linking, and then wrapping, fixing and installing.
[0122] The added amount of toluene is 9 times the mass of EVA.
[0123] The specific conditions of the drying and aging are: drying temperature 80° C., time 4 hours; aging temperature 60° C., time 24 hours.
[0124] The specific conditions of the composite cross-linking are: temperature of 150° C. and cross-linking time of 15 min.
[0125] The radius of the semicircular long strip solar panel is 200 mm and the length is 1500 mm.
[0126] Example 2
[0127] The difference between this embodiment and Embodiment 1 is that the mass ratio of the first fluorocarbon resin to the second fluorocarbon resin is 1:2.
[0128] Example 3
[0129] The difference between this embodiment and Embodiment 1 is that the mass ratio of the first EVA resin to the second EVA resin is 2:1.
[0130] Comparative Example 1
[0131] The difference between this comparative example and Example 1 is that the fluorocarbon resin is the first fluorocarbon resin.
[0132] Comparative Example 2
[0133] The difference between this comparative example and Example 1 is that the fluorocarbon resin is the second fluorocarbon resin.
[0134] Comparative Example 3
[0135] The difference between this comparative example and Example 1 is that the curing agent is dicyclohexyl aliphatic diisocyanate.
[0136] The NCO content of the dicyclohexyl aliphatic diisocyanate is ≥31.8%, and the viscosity at 25° C. is 30 mPa·s.
[0137] The dicyclohexyl aliphatic diisocyanate was purchased from Wanhua, HMDI.
[0139] Comparative Example 4
[0140] The difference between this comparative example and Example 1 is that the raw materials for preparing the film layer, by weight percentage, are 45% fluorocarbon resin, 12% curing agent, 1% dispersant, 15% titanium dioxide, 0.3% leveling agent, and the solvent is supplemented to the remainder to 100%.
[0141] Comparative Example 5
[0142] The difference between this comparative example and Example 1 is that the coupling agent is 3-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0143] The mass ratio of the 3-aminopropyltriethoxysilane to the γ-methacryloxypropyltrimethoxysilane is 1:4.
[0144] Comparative Example 6
[0145] The difference between this comparative example and Example 1 is that the coupling agent is 3-aminopropyltriethoxysilane or 3-mercaptopropyltriethoxysilane.
[0146] The mass ratio of the 3-aminopropyltriethoxysilane to the 3-mercaptopropyltriethoxysilane is 1:2.
[0147] Comparative Example 7
[0148] The difference between this comparative example and Example 1 is that the mass ratio of the first EVA resin to the second EVA resin is 1:5.
[0149] Comparative Example 8
[0150] The difference between this comparative example and Example 1 is that the cross-linking agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
[0151] Comparative Example 9
[0152] The difference between this comparative example and Example 1 is that the raw materials for preparing the EVA layer include, by weight, 100 parts of EVA resin, 5 parts of cross-linking agent, 0.1 parts of ultraviolet light absorber, 0.08 parts of free radical scavenger, and 3 parts of inorganic additives.
[0153] Comparative Example 10
[0154] The difference between this comparative example and Example 1 is that the raw materials for preparing the EVA layer, by weight, include 100 parts of EVA resin, 5 parts of cross-linking agent, 0.5 parts of silane coupling agent, 0.1 parts of ultraviolet light absorber, 0.08 parts of free radical scavenger, and 8 parts of inorganic additives.
[0155] Performance Testing
[0156] The visible light transmittance and EVA peel strength of the CPC layer were tested with reference to GB / T 31034-2014 "Insulating backsheet for crystalline silicon solar cell modules". When testing the EVA peel strength, the EVA layer was prepared using the EVA raw material described in the present invention. UV test conditions: 250kwh / m 2 , test the visible light transmittance and yellowing index Δb after UV test, the initial yellowing index is 0, and the test method refers to GB / T 31034-2014. The conditions of wet heat aging treatment: humidity 85%, temperature 85℃, aging time 3000h, test the visible light transmittance and yellowing index after wet heat aging. The results are shown in Table 1.
[0157] Table 1 Measurement results
[0158]
[0159] According to statistics, the semicircular long strip solar panels prepared in Examples 1 to 3 of the present invention have a CPC layer that not only has a high transmittance, but also has excellent weather resistance and aging resistance, and has good adhesion to the EVA layer, thereby ensuring the power generation effect of the solar panel while increasing its lifespan. Comparative Example 1 does not add the second fluorocarbon resin, Comparative Example 2 does not add the first fluorocarbon resin, Comparative Example 3 does not use a specific curing agent, Comparative Example 4 does not modify titanium dioxide, Comparative Example 5 does not add 3-mercaptopropyl triethoxysilane, Comparative Example 6 does not add γ-methacryloxypropyl trimethoxysilane, Comparative Example 7 does not add too much second EVA, Comparative Example 8 does not add triallyl isocyanurate, Comparative Example 9 does not add a silane coupling agent, Comparative Example 10 does not add too much inorganic additives, the prepared CPC layer has a low transmittance, poor weather resistance and anti-wet heat aging performance, and the bonding strength between the CPC layer and the EVA layer will also affect the life of the solar panel. Therefore, the new CPC material prepared by the raw materials and methods described in this application as a backplane not only has a high transmittance, but also has excellent weather resistance and aging resistance. The prepared solar panel is not only beautiful, but also greatly reduces wind resistance and improves use efficiency. At the same time, the solar panel is light in weight, low in installation cost, and easy and quick to install.
[0160] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A semicircular long strip solar panel, characterized in that: From bottom to top: glass fiber board / PTE layer, EVA layer, strip battery sheet, EVA layer, CPC layer; The CPC layer includes a PET base film and film layers on both sides of the PET base film; The raw materials for preparing the film layer are, by weight percentage, 40% to 50% fluorocarbon resin, 10% to 15% curing agent, 0.1% to 2% dispersant, 10% to 20% modified titanium dioxide, 0.1% to 0.5% leveling agent, and the solvent is added to make up the balance to 100%; The fluorocarbon resin includes a first fluorocarbon resin and a second fluorocarbon resin; The first fluorocarbon resin has a solid content of 59% to 61%, a hydroxyl value of 33 to 43 mgKOH / g, a number average molecular weight of 12,000 to 16,000, an acid value of <1 mgKOH / g, and a viscosity of 500 to 1,000 cp; The second fluorocarbon resin has a solid content of 49% to 51%, a hydroxyl value of 49 to 59 mgKOH / g, a viscosity of 340 to 500 cp, a fluorine content of 22% to 24%, and a number average molecular weight of 15,000 to 20,000; The raw materials for preparing the EVA layer include, by weight, 95-105 parts of EVA resin, 2-8 parts of crosslinking agent, 0.05-1 part of silane coupling agent, 0.05-0.2 part of ultraviolet light absorber, 0.05-0.1 part of free radical scavenger, and 2-4 parts of inorganic auxiliary agent.
2. The semicircular strip solar panel according to claim 1, characterized in that: The thickness of the EVA layer is 120-170 μm; the thickness of the PET base film is 100-150 μm, the light transmittance is ≥85%, and the UV light blocking rate of 250-360 nm is ≥90%; the thickness of the film layer is 15-30 μm.
3. The semicircular long strip solar panel according to claim 1, characterized in that: The mass ratio of the first fluorocarbon resin to the second fluorocarbon resin is 1:(0.5-2).
4. The semicircular strip solar panel according to claim 1, characterized in that: The curing agent is polyisocyanate resin.
5. The semicircular long strip solar panel according to claim 4, characterized in that: The polyisocyanate resin is an aliphatic polyisocyanate resin containing hexamethylene diisocyanate.
6. The semicircular long strip solar panel according to claim 5, characterized in that: The NCO content of the polyisocyanate resin is 23% to 24%, the viscosity at 23° C. is 630 to 860 mPa·s, and the content of hexamethylene diisocyanate monomer is less than 0.25%.
7. The semicircular long strip solar panel according to claim 1, characterized in that: The preparation method of the modified titanium dioxide comprises the following steps: hydrolyzing the coupling agent in an ethanol aqueous solution with a concentration of 80 wt / %, adding titanium dioxide, stirring at 55-65° C. for 2-4 hours, filtering, and drying at 100° C. for 12 hours to obtain the modified titanium dioxide.
8. The semicircular long strip solar panel according to claim 7, characterized in that: The coupling agent is 3-aminopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane and gamma-methacryloxypropyltrimethoxysilane.
9. The semicircular long strip solar panel according to claim 1, characterized in that: The EVA resin includes a first EVA resin and a second EVA resin.
10. A method for preparing a semicircular long strip solar panel according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. After mixing the raw materials for preparing the EVA layer, add toluene, stir and dissolve evenly, and perform ultrasonic treatment for 20 to 30 minutes to obtain an EVA layer solution; S2, coating the EVA layer solution on the glass fiber board / PTE layer, drying, aging and cooling; S3, coating the EVA layer solution on the CPC layer, drying, aging and cooling; S4, placing the strip-shaped battery sheet between two EVA layers, compounding and cross-linking, and then wrapping, fixing and installing.